IFPRI by the numbers - International Food Policy Research Institute (International Food Policy Research Institute, 2017)
For more than 40 years, the International Food Policy Research Institute (IFPRI) has been providing research-based policy solutions to reduce poverty and end hunger and malnutrition. A recent stocktaking of the impact of IFPRI’s work over this period, based on just a small number of projects, shows our research has contributed to improving the lives of at least 200 million people. This was accomplished by informing policy decisions and investments made by governments, funders, and other partner organizations around the world. And since many important projects were not included in this calculation, we can assume that the actual number of people who benefited is much higher. IFPRI thanks its many funding and implementing partners, with whom we share these achievements.